A case of inferior lumbar hernia - Sharma, Vidhyasagar M.; Akruwala, Sushil D.; Desai, Shashank; Dave, Rajendra I. (International Journal of Research in Medical Sciences, 2017)
In this article we report a case of inferior lumbar hernia. The patient underwent preperitoneal meshplasty. The patient is well on follow up with no recurrence. The relevant literature has been reviewed and management discussed in brief.